Pengaruh Kompensasi terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kecamatan Salimpaung - Suci, Rahmi; Syamsir, Syamsir (JESS (Journal of Education on Social Science); Vol 2 No 1 (2018): Social Issues in Public ServiceDO - 10.24036/jess/vol2-iss1/56, 2018)
This study reveal ed  the effect of compensation on the performance of nagari apparatus in the management of nagari finance in Kecamatan Salimpaung, Tanah Datar District. This study  use d  associative quantitative method. The population in this study  is all nagari apparatus  in Kecamatan Salimpaung as many as 42 people consisting of nagari secretary, nagari treasurer, and s taff s . The sample of this study consisted of 38 respondents determined by multistage random sampling technique and us ed  slovin formula. The data of this study  were collected through questionnaire and analyzed with  multiple linear regression analysis technique. The results of this study indicate d  that compensation simultaneously ha d  a significant effect on the performance of nagari apparatus  in the management of nagari finance in Kecamatan Sa limpaung. Partially, finansial  compensation ha d  a significant influence on the performance of nagari apparatus  in nagari finansial  management; while non- finansial  compensation ha d  no significant effect on the performance of the nagari apparatus  in the management of nagari finance in Kecamatan Salimpaung.